Opportunities and Problems of Analysis of Mortality from Myocardial Infarction According to Medical Certificates of Death (on the Example of the Tula Region) - Drapkina, O M; Samorodskaya, I V; Vaisman, D Sh (Kardiologiia, 2019)
to analyze the quality of completion medical certificates of death (MCD) of residents of the Tula region, in which in 2017 acute and subsequent myocardial infarction (MI) was listed as the underlying cause of death (UCD) or as multiple causes of death (MC). From the electronic database (DB) of MCD of residents of Tula region for 2017 we selected all MSD in which MI was written down irrespective of a section of MCD. A total of 689 MSD (43.8% men and 56.2% women) were analyzed. Mean age of the deceased was 72.6±11.3 years (men 67.25±0.62; women 76.7±9.8; p<0.001). Multimorbid pathology was registered in 31.5% of the deceased. In 77.9% of cases myocardial infarction was selected as the UCD and in 22.1% - as a complication of other diseases. Among registered MI complications were hemotamponade (24.5%), cardiogenic shock (3.6%), ventricular fibrillation (0.3%), heart failure (50.2%). Complications of MI were not listed in 3.9% of MCD. Analysis of MCD showed that their completion did not comply with established ICD-10 rules and recommendations of Ministry of Health of RF; all lines were filled out only in 1% of completed MCD. Also, problems of determining the initial cause of death when myocardial infarction occurred in the presence of multimorbid pathology were revealed. Mortality analysis using solely UCD leads to decreasing mortality rates from MI, and unsatisfactory quality of filling the MCD decreases the ability to identify MC, that prevents the correction of priorities in the organization of medical care. The revealed problems of coding causes of death require urgent solutions from the professional community of cardiologists, pathologists, and the Ministry of Health.